Circulating 'lncRNA OTTHUMT00000387022' from monocytes as a novel biomarker for coronary artery disease. Issue 3 (7th February 2016) - Cai, Yue; Yang, Yujia; Chen, Xiongwen; Wu, Genze; Zhang, Xiaoqun; Liu, Yukai; Yu, Junyi; Wang, Xinquan; Fu, Jinjuan; Li, Chuanwei; Jose, Pedro A.; Zeng, Chunyu; et al.
Abstract : Aims: Long non-coding RNAs (lncRNAs) have been found to be involved in the pathogenesis of coronary artery disease (CAD). However, it remains to be established whether or not circulating lncRNAs can serve as biomarkers of CAD. Methods and results: Using a microarray-based lncRNA expression profiling, we found 86 lncRNAs that were differentially expressed in circulating peripheral blood monocytes and plasma from 15 CAD patients and 15 control subjects. After choosing a consistent criterion (average normalized intensity ≥7 with significance <0.005) and confirmed by quantitative PCR, only three lncRNAs (CoroMarker, BAT5, and IL21R-AS1) remained as candidate CAD biomarkers. Using the analysis of area under the curve (AUC) of the receiver-operating characteristic in another pilot group and another larger cohort, CoroMarker was found to be the best candidate biomarker for CAD with an AUC of 0.920 and 95% confidence interval of 0.892–0.947. CoroMarker was independent from known CAD risk factors and other cardiovascular diseases. In a prospective study, we found that the sensitivity and specificity of CoroMarker were 76 and 92.5%, respectively. Functional enrichment analysis showed CoroMarker to be clustered with genes positively associated with signal transduction, transmembrane transport, synaptic transmission, and innate immunity and negatively associated with inflammation. These findings were validated in THP-1 cells; CoroMarker siRNA treatment decreased the concentrations of proinflammatory cytokines [interleukin (IL)-1β, IL-6, and tumour necrosis factor α] in the culture medium. Conclusion: The present study suggests that CoroMarker is a novel and specific biomarker of CAD.